Prokopio de Cezareo, enigma historiisto de la epoko de Justiniano (sesa jarcento p.K.) - Greatrex, Geoffrey (Universala Esperanto-Asocio, 2008)
The author offers a brief survey of the history of the sixth century, and in particular of the reign of Justinian. He analyses both the positive and negative aspects of the perio, e.g. natural disasters in the latter category. All of this serves as an introduction to a discussion of the works of the principal historian of the period, Procopius of Caesarea. The life and career of the historian are discussed, followed by a more detailed analysis of his well-known work, the Secret History (or Anecdota). The author defends its trustworthiness against some modern critics and offers modern parallels for how it came to be written and for one episode in it. // L'auteur propose d'abord une brève analyse du VIe siècle, en particulier du règne de Justinien. Il étudie les aspects positifs et négatifs de la période, par exemple, les catastrophes naturelles. Tout cela sert d'introduction à une présentation des oeuvres de l'histoirien le plus important de cette époque, Procope de Césarée. Suit une évocation de la vie et de la carrière de cet historien ainsi qu'une analyse plus élaborée de son oeuvre la plus connue, l'Histoire secrète (Anecdota). L'auteur défend la fiabilité de l'oeuvre contre les critiques de certains auteurs modernes et propose des parallèles modernes qui éclairent sa genèse et l'un des épisodes qu'elle relate.
Procope de Césarée, historien énigmatique de l'époque de Justinien (VIe siècle ap.J.C.)
Procopius of Caesarea, enigmatic historian in the age of Justinian (6th century AD)
Keywords: Secret History; Theodora; Belisarius; Justinian; Justiniano; Procopius; bizanca historiografio; Teodora; Belisario; Sekreta Historio; historiografio klasikstila; Anecdota; Justinien; Procope; Byzantine historiography; Classicising historiography; Historiographie classicisante; Historiographie byzantine; Bélisaire; Théodora; Prokopio